The Effect of Income Tax Article 21 Implementation, Fiscal Correction, and Deferred Tax on Corporate Income Tax: Evidence from Automotive and Component Firms Listed on the Indonesia Stock Exchange - Warsito Warsito (Priviet Social Sciences Journal, 2024)
This study examines the effect of Income Tax Article 21 (PPh 21), fiscal correction, and deferred tax on corporate income tax in automotive and component sub-sector companies listed on the Indonesia Stock Exchange during the period 2009–2013. The study employs a quantitative approach using secondary data obtained from published financial statements, with a sample of twelve companies selected through purposive sampling. Data analysis is conducted using multiple linear regression to evaluate both partial and simultaneous effects of the independent variables on corporate income tax. The results indicate that PPh 21 has a positive and significant effect on corporate income tax, suggesting that employee income tax policies contribute substantially to corporate tax burden. Deferred tax is also found to have a positive and significant effect, reflecting the impact of temporary differences between accounting and taxable income on future tax obligations. In contrast, fiscal correction shows a positive but insignificant effect, indicating a relatively limited role in influencing corporate income tax within the observed sample. Simultaneously, all independent variables are found to have a significant effect on corporate income tax, with PPh 21 and deferred tax emerging as the dominant factors. These findings highlight the importance of effective tax planning and financial reporting strategies in managing corporate tax obligations. The study contributes to the literature by providing empirical evidence on the role of tax-related variables in corporate taxation, particularly within the automotive industry in Indonesia.